The Jurisprudence of Divine Law (al-Sunan al-Ilāhiyyah) and Sunanī Culture - Ahmad, Azmi Taha al-Sayyid (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2023)
This study seeks to identify Divine Law (al-Sunan al-Ilāhiyyah) and to thoroughly construe its multilateral truth. The Divine Law is a system of overarching laws constituted and accurately designed by Allah (SWT), ruling the different areas of existence. Perpetual, well-integrated, and cohesive, these laws are meant to act as guidelines for mankind, so that life can progress accordingly, uncoerced. The study comprises two sections: a theoretical section that aims to identify, as accurately as possible, the truth of Divine Law, designated as the “Jurisprudence of Divine Law” (al-Sunan al-Ilāhiyyah); and a practical section that aims to apply the theoretical part of the Divine-Law (Sunanī) culture to real life. The study concludes that there is a distinction between cosmic, natural laws and those regulating human life. It also lays emphasis on the integration and interconnectedness of the Divine Law in order to grasp its operational mechanisms in human life.